2010
DOI: 10.3354/dao02157
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida Type I pilus system contributes to host colonization but not invasion

Abstract: The host-adherence strategies employed by Aeromonas salmonicida subsp. salmonicida, the etiological agent of an infectious bacteremia of salmonids, are poorly understood. In addition to the outer protein coat or S-layer, A. salmonicida has both Type I and Type IV pili loci. The A. salmonicida Type I or Fim pilus is encoded by an operon with genes for a chaperone, an usher, and 3 pilus subunits and is predicted to be similar to the Pap fimbriae of uropathogenic Escherichia coli, which are considered significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 24 publications
(32 reference statements)
0
31
0
Order By: Relevance
“…In Escherichia coli, Neu5Ac has been shown to promote type I fimbria production, while GlcNAc has an inhibitory role (41). As type I fimbriae are important adhesion and virulence factors in A. salmonicida (42), one can speculate that Atlantic salmon mucins exert similar changes in fimbria production. The presence of GlcNAc may signal to the pathogen that it is in the mucus niche, and downregulating such factors may in turn free up more resources for growth.…”
Section: Discussionmentioning
confidence: 98%
“…In Escherichia coli, Neu5Ac has been shown to promote type I fimbria production, while GlcNAc has an inhibitory role (41). As type I fimbriae are important adhesion and virulence factors in A. salmonicida (42), one can speculate that Atlantic salmon mucins exert similar changes in fimbria production. The presence of GlcNAc may signal to the pathogen that it is in the mucus niche, and downregulating such factors may in turn free up more resources for growth.…”
Section: Discussionmentioning
confidence: 98%
“…The A. salmonicida S-layer and type I pilus system have previously been shown to contribute to A. salmonicida adhesion to the salmon intestine ex vivo (57).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported the involved virulence factors in fish infections (11,17,36). The primary challenge in establishing an unequivocal link between the Aeromonas genus and pathogenesis is the extremely complicated taxonomy.…”
mentioning
confidence: 99%